2011
DOI: 10.1063/1.3658017
|View full text |Cite
|
Sign up to set email alerts
|

InGaAs-based bow-tie diode for spectroscopic terahertz imaging

Abstract: Suitability of InGaAs-based bow-tie diodes for a spectroscopic terahertz imaging is demonstrated by inspecting explosive simulators packed in a thick plastic container. The transmission images were obtained within the frequency range of 0.58-2.52 THz at room temperature using optimized bow-tie diode connection scheme. Content of sucrose and tartaric acid in the test samples was discriminated. Measured absorbance was found to be in a good correlation with Fourier spectroscopy data. Performance of room temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 20 publications
0
26
0
3
Order By: Relevance
“…Development of stand-alone, real-time frequency sensitive imaging systems is in the prime interest due to the portability and price issues of currently available systems [2]. Special attention is paid to compact room-temperature THz security systems which can provide the ability to screen objects inside packages without opening them, and to identify chemical content via spectroscopy [3,4,5]. Implementation of such an imaging system requires frequency selective THz sensors with high sensitivity, fast response time, high dynamic range, and low noise-equivalent-power (NEP).…”
Section: Introductionmentioning
confidence: 99%
“…Development of stand-alone, real-time frequency sensitive imaging systems is in the prime interest due to the portability and price issues of currently available systems [2]. Special attention is paid to compact room-temperature THz security systems which can provide the ability to screen objects inside packages without opening them, and to identify chemical content via spectroscopy [3,4,5]. Implementation of such an imaging system requires frequency selective THz sensors with high sensitivity, fast response time, high dynamic range, and low noise-equivalent-power (NEP).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar way, a pure PTFE pellet of 0.36 g and the same 1.3 mm thickness as prepared as a reference material. More detail on the sample preparation and spectroscopy can be found elsewhere [9]. …”
Section: Raster-scan Spectroscopic Imagingmentioning
confidence: 99%
“…It is clearly seen that the explosive simulator containing the tablet exhibits differently "shadowed" images due to stronger absorbance at each frequency. In contrast, the "color" of the pure PTFE reference sample practically shows no changes since this sample has no spectral peculiarities in its spectra [7,14]. The comparison of images of metallic washers at different frequencies illustrates an increase in spatial resolution at higher THz frequencies.…”
Section: Bow-tie Diodes For Terahertz Imaging: a Comparative Studymentioning
confidence: 99%
“…Moreover, it was demonstrated that an InGaAs-based bow-tie diode is well suited for fast spectroscopic THz imaging. Measurements performed with the BT diodes at 2.52THz frequency have shown that, without losing any THz image quality, images can be recorded via increasing the THz beam modulation frequency and the scanning speed up to 30kHz and 300mm/s, respectively [7]. If the bow-tie diode is replaced by a bandwidth limited commercial pyroelectric detector, it results in a smoothed profile leading to an image blurring effect and incorrect transmittance values.…”
Section: Bow-tie Diodes For Terahertz Imaging: a Comparative Studymentioning
confidence: 99%
See 1 more Smart Citation